A Snapshot Survey of Uterotonic Administration Practice During Cesarean Section: Is There a Difference Between the Attitudes of Obstetricians and Anesthesiologists? - Nuray Camgoz Eryilmaz; Selin Erel; D. Berrin Gunaydin (Medicina, 2025)
Background and Objectives: We aimed to evaluate the current uterotonic administration practices among anesthesiologists and obstetricians and gynecologists (OBGYNs) during cesarean section (CS), focusing on variations in approaches for low- and high-risk postpartum hemorrhage (PPH) cases. The objective was to identify key differences and provide evidence that could contribute to the development of standardized national protocols for uterotonic usage. Materials and Methods: A snapshot online survey was employed between October 2021 and January 2022 and distributed to anesthesiologists and OBGYNs from university-affiliated, government, and private hospitals across Turkey, consisting of 23 questions addressing demographic data, institutional PPH rates, first-line uterotonic choices, administration methods, and dose adjustments for low- and high-risk PPH cases. Specific questions also targeted uterotonic usage in the presence of comorbidities such as pre-eclampsia and cardiac disease. Results: There were 204 responses (54% anesthesiologists and 46% OBGYNs) out of 220, yielding a response rate of 92.7%. Oxytocin was the most common first-line uterotonic for CS with low-risk PPH (99.1% of the anesthesiologists and 96.8% of the OBGYNs). In total, 60% of the anesthesiologists favored an intravenous (IV) bolus followed by infusion, while 56.4% of the OBGYNs preferred IV infusion alone (p < 0.001). For CS with high-risk PPH, approximately half of the participants reported increases in oxytocin dose, while 26.4% of the anesthesiologists and 20.2% of the OBGYNs opted for combined oxytocin and carbetocin use. During intrapartum CS, 69.1% of anesthesiologists and 77.7% of OBGYNs reported no change in dose. However, 11.8% of the anesthesiologists indicated combining oxytocin and carbetocin (p < 0.05). In managing pre-eclampsia and cardiac disease, the anesthesiologists were likely to reduce uterotonic doses (15.5%) and avoid methylergonovine (35.5%) compared to the OBGYNs, who reduced doses less frequently (4.3%), but 79.8% of the OBGYNs avoided methylergonovine (p < 0.001). Conclusions: There was considerable variability in uterotonic administration practices between the anesthesiologists and OBGYNs.